Analysis of Behavioral Change in Banda Aceh City Community Two Years After the Covid-19 Pandemic - Dasrin Dasrin; Radhiah Zakaria; Maidar Maidar; Asnawi Abdullah; Fahmi Ichwansyah (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
COVID-19 is a respiratory disease that poses a current threat. Public non-compliance with health protocols can negatively impact COVID-19 transmission. A person's behavior significantly impacts their health. The design of this research is quantitative descriptive with Cross Sectional design, the population in the study is all productive-age Banda Aceh residents totaling 252,899 people and the sample in this study totaling 399 people who have met the inclusion criteria with Accidental Sampling technique using statistical analysis of the t-test (paired-samples t test) and One Way Anova Repeated Measure Test using the Stata 14 program. The results of the study show that there are significant changes in community behavior after 2 years of the Covid-19 pandemic for 3 time periods (the beginning of the Covid-19 pandemic (2020), 1 year ago (2021) and currently (2022)) related to the 5M Health Protocol (p-value 0.0000), Barriers to Mask Use (p-value 0.0000), Information Related to Handling Covid-19 (p-value 0.0001), Perception (p-value 0.0000), Attitude (p-value 0.0000, and Behavior Towards Covid-19 (p-value 0.0000). However, the t-test results showed no significant change in community behavior in the Attitude variable between 1 year ago (2021) and now (2022) (p-value 0.8997) and in the Information Regarding Handling of Covid-19 variable between the beginning of the pandemic (2020) and now (2022) (p-value 0.3048). The most dominant change in community behavior after 2 years of the Covid-19 pandemic was in the 5M Health Protocol variable, in the period 1 year ago (2021) and now (2022), with a p-value of 0.0000 and a difference of 3.24. It is hoped that the community will continue to strive to improve their health behavior, so that the level of public health is maintained, and hopefully we are truly free from the Covid-19 pandemic